Optimalisasi Software Akuntansi Berbasis Ekonomi Digital untuk Meningkatkan Akuntabilitas di Pondok Pesantren At-Taqwa Al Islamiy Desa Wringinputih Kecamatan Borobudur Kabupaten Magelang - Nugroho, Wawan Sadtyo; Prasetya, Wahyu Anggit; Ibrahim, Muhamad Wahid (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
The urgency of this activity is that Islamic Boarding School financial reports have not been recorded based on the provisions of Financial Accounting Standards (SAK). The aim of the service activities is to increase accountability in the preparation of financial reports and financial management as well as the implementation of Islamic boarding school accounting applications (SANTRI). It is hoped that by holding training or provision, it will be able to provide adequate knowledge so that it can be implemented in Islamic boarding schools so that they are able to prepare financial reports in accordance with the Accounting Standards rules that apply in Indonesia. At-Taqwa Al Islamiy Islamic Boarding School (Ponpes) is the target of this program activity. The Islamic boarding school is one of the Islamic boarding schools located in Borobudur District, Magelang Regency, Central Java. With quite a few students, the Islamic boarding school's financial management refers to the applicable PSAK ETAP so that existing financial reports can provide maximum information according to the detailed needs of funders and donors. It is hoped that the SANTRI software can help in carrying out financial records in accordance with Islamic boarding school needs.